Dual carbon-modified nickel sulfide composites toward high-performance electrodes for supercapacitors. Issue 1 (6th December 2018) - He, Jiapeng; Guo, Can; Zhou, Shaowen; Zhao, Yinlong; Wang, Qingpeng; Yang, Shun; Yang, Jiaqin; Wang, Qinghong
Abstract : Dual carbon-modified nickel sulfide composites have been facilely prepared and they deliver excellent energy storage performance for supercapacitors. Abstract : Composites with reduced graphene oxide (rGO) modification or carbon-coated structures are usually constructed to enhance the electrochemical performance of electrode materials. Herein, we develop a sequential freeze-drying, calcination and sulfidation strategy to prepare dual carbon-modified nickel sulfide composites (Ni3 S2 @C/rGO). Owing to the ultrasmall particle size, stable structure and high electrical conductivity, the as-prepared composites exhibit enhanced performance with high specific capacitance (1023.44 F g −1 at a current density of 5 A g −1 ), good rate capability (848 F g −1 at a current density of 20 A g −1 ) and long-term cycling stability (70.1% retention over 5000 cycles) as electrode materials for supercapacitors. Moreover, the asymmetric supercapacitor displays a good cycle life and a superior energy density of 52.5 W h kg −1 at a power density of 750 W kg −1 . The facile fabrication and excellent electrochemical performances of Ni3 S2 @C/rGO demonstrate that constructing dual carbon-modified composites is a promising strategy for high-performance electrode materials.